Open source software : implementation and management - Kavanagh, Paul.; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier Digital Press, 2004)
In 2004/5, over half of IT professionals will be looking at open source, most for the first time. This book provides key tools for System administrators, Network Administrators, IT project managers, and consultants who must evaluate and deploy open source software. This book details open source successes so far, explains which scenarios are the most realistic opportunities now, then gives the details needed to select these solutions, adopt the best tools and practices, introduce them to an organization, implement and manage them. The IT professional can use this book to review opportunities in their organization, evaluate components such as Apache, Linux, and OpenOffice against systems they know, and follow up in detail on their specific interests here and through referred resources. *Deployment scenarios categorized by function and industry *Rules of thumb on where and when open source software is or is not the right choice *Roadmaps for deployment in terms of the components of open source.
Open source software : definitions and history -- Where open source is successful -- Open source : the good, the bad, and the ugly -- Five immediate open source opportunities -- Five more open source opportunities -- Operating systems -- Open source server applications -- Open source desktop applications -- How open source software is developed -- Managing system implementation -- Application architecture -- The cost of open source systems -- Licensing.
Includes bibliographical and web references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Safari Books Online
Keywords: Linux; Apache (Computer file : Apache Group); Linux; Apache (Computer file : Apache Group); Apache (Computer file : Apache Group); Linux; Open source software; Shareware (Computer software); Operating systems (Computers) -- Management; Computer software -- Development; REFERENCE -- General; Open source software; Shareware (Computer software); Operating systems (Computers) -- Management; Computer software -- Development; Computer software -- Development; Open source software; Shareware (Computer software); Electronic books